INOVASI PRODUKSI GARAM DI DESA PALUH SIBAJI, KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG SUMATERA UTARA - Suprianto, Suprianto; Siregar, Muhammad Fadlan; Syahputra, Syofyan Anwar; Fahmi, Muhammad Ikhwan; Frianto, Herri Trisna; Sumantri, Ahmad; Harianto, Budi; Lestari, Meidi Wani; Permata Bunda, Yola (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Community Service Activities for Salt Farmers to Increase Salt Production in Paluh Sibaji Village, Pantai Labu District, Deli Serdang Regency, North Sumatra were carried out by providing assistance in the form of building evaporation houses and providing material assistance for repairing and building goat pens for salt farmers. The purpose of this activity is for salt farmers to increase their salt production capacity by increasing the speed and effectiveness of the production process. The method used is the construction method of a semi-elliptical evaporation house whose supports are made of elastic plastic pipes with iron reinforcements inside the pipe so that water vapor will flow through the pipes and plastic formed in a semi-elliptical construction. Community service activities were carried out by building an evaporation house for the salt production process. In addition, the community service team provided material assistance for the construction and repair of goat pens for salt farmers. Livestock farming for salt farmers is a common side business carried out by salt farmers to support household economic needs. The results of the activity were the construction of a semi-elliptical evaporation house that will be used by salt farmers to increase salt production and assistance to salt farmers in the form of material assistance for the construction and repair of salt farmer's livestock pens.